Effects of a social regulation-based online learning framework on students' learning achievements and behaviors in mathematics. (January 2021) - Hwang, Gwo-Jen; Wang, Sheng-Yuan; Lai, Chiu-Lin
Abstract: Most university degrees often require students to demonstrate proficiency in mathematics, which is the basic requirement in many fields, such as science, engineering, or technology. Mathematical knowledge is so common as to be essential in higher education. Although mathematical skills are crucial to the success of study in many domains, a large number of students are not willing to study related courses. Anxiety and pressure triggered by previous failures in mathematic learning are considered as the reason. The online learning environment provides students with opportunities to exchange opinions with others and facilitate their self-regulated learning. Scholars believe that the learning performances of students can be enhanced if they make reference to other students' learning strategies during the study process. The practice of making references to other students' learning strategies and mutually monitoring each other during the study process is called social regulation. The study efficiency of social regulation in learning mathematics will need to be verified. This study has adopted a social regulation-based online learning approach for assisting students in achieving learning goals with peers' power. At the same time, this study conducted an experiment with an experimental group and a control group. The social regulation-based online learning approach was used by the experimental group while the conventional self-regulated learning approach was used by the control group. According to the results, the social regulation-based online learning approach enhances students' learning achievements and learning motivations in mathematics. Based on the results of the sequential pattern analysis for investigating the online learning behaviors of the two groups of students, students who use the social regulation-based online learning approach have more positive online learning behaviors, such as reading the supplementary materials regarding the wrongly answered questions and revising the notes. On the contrary, students who use the conventional self-regulated learning approach only pay attention to the results of tests and feedback provided by their teacher. They seldom have behaviors of looking at the supplementary materials, adding or deleting notes. With the above verification, the developed system of this study not only enhances students' learning performances, but also guides them to have more meaningful learning behaviors in mathematics. Highlights: A social regulation-based online learning approach is proposed. An experiment was conducted to evaluated the performance of the learning approach. The approach has been applied to a high school math course. The approach improved the students' learning achievement and learning motivation. The approach stimulated students to have more positive learning behaviors.